Institutional Impact on Work-related Values in Chinese Organizations - Alas, Ruth (Journal of business ethics, 2008)
This study in 29 Chinese organizations contributes to our understanding about work-related values in China. Empirical research in Chinese organizations indicates differences in work-related values between different age groups. The authors compared people (older age group) with work experience from the pre-reform period – pre-1978 China, with those who started their work life in a society that had already changed and become open to foreign investments (younger age group). The authors created a model of institutionally sensitive work-related values. The results could help multinational companies achieve competitive advantage.